Feminism through the Lens of the Gen Z (American Journal of Youth and Women Empowerment, 2023)
With minimal pieces of literature to explain the phenomenon, this study explores the experiences of Filipino Generation Z (Gen Z) on feminism. Ten participants, born between 1997 to 2012, from diverse backgrounds, were selected and interviewed using semi-structured, open-ended questions. The researchers discovered that the experiences of Gen Z are rooted in their perceptions of feminism. Their perceptions view feminism as women’s empowerment that seeks gender equality and is anchored as a feminist movement. Cultural identity and practice, socio-political affiliation, and social media influence how they perceive feminism. However, it is misunderstood as a claim for women’s superiority toward men or other genders, and gender stereotypes still exist. Gender discrimination and sexism urge the need to advance feminism. Hence, educational institutions, local governments, and non-governmental and private organizations must provide avenues to deepen Gen Zs understanding, appreciation, and involvement in feminism and feminist movements. Further research exploring specific contexts or cases about it is encouraged.